2004
DOI: 10.1001/jama.292.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Fetal Cells With Multilineage Potential to Maternal Tissue

Abstract: Context During pregnancy, fetal CD34 + cells enter the maternal circulation, persist for decades, and create a state of physiologic microchimerism. Many studies have confirmed the residual presence of fetal cells in maternal blood and tissues following pregnancy. Fetal cells may respond to maternal injury by developing multilineage capacity in maternal organs. Objective To verify that fetal microchimeric cells express markers of epithelial, leukocyte, and hepatocyte differentiation within maternal organs. Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
139
1
10

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 242 publications
(158 citation statements)
references
References 32 publications
8
139
1
10
Order By: Relevance
“…Whether FMCs include a functional myogenic precursor remains unclear. Consistent with FMC phenotypes reported in other studies [2,44], the majority of FMCs identified in this study were hematopoietic. Despite previous reports where hematopoietic cells have beneficially contributed to muscle differentiation during repair [18], they did not produce this outcome in our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Whether FMCs include a functional myogenic precursor remains unclear. Consistent with FMC phenotypes reported in other studies [2,44], the majority of FMCs identified in this study were hematopoietic. Despite previous reports where hematopoietic cells have beneficially contributed to muscle differentiation during repair [18], they did not produce this outcome in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Small numbers of these semiallogeneic cells engraft in maternal organs and persist for decades [1,2]. Although this phenomenon seems ubiquitous in humans and mice, its clinical significance is largely unknown.…”
mentioning
confidence: 99%
“…Indeed in a female, liver male cells-precisely analyzed by PCR-showed that these originated from a stillbirth which occurred 20 years earlier (25). The presence of fetal mesenchymal stem cells in the marrow of females has recently been shown (26), while evidence for the presence of fetal cells differentiated in several types of peripheral organs in mothers of male babies born several years or decades before were also obtained (27).…”
Section: Discussionmentioning
confidence: 99%
“…Natural chimerism occurs in parous and pregnant females as a result of the trafficking of fetal cells to the maternal circulation during pregnancy and their long-term persistence after delivery. [5][6][7][8] Fetal microchimeric cells (FMCs) have been identified in larger numbers in pathological conditions, including cancer, inflammatory diseases or reparative processes as compared with normal tissues. [9][10][11][12][13][14][15] This recruitment capacity associated with their described plasticity 7,16 has suggested that the study of fetal cell microchimerism can inform on homing and engraftment of host stem cells in response to tissue injury.…”
mentioning
confidence: 99%